The Roles of E93 and Kr-h1 in Metamorphosis of Nilaparvata lugens - Li, Kai Long; Yuan, San Yue; Nanda, Satyabrata; Wang, Wei Xia; Lai, Feng Xiang; Fu, Qiang; Wan, Pin Jun (Frontiers in Physiology, 2018)
Metamorphosis is a crucial process in insect development. Ecdysone-induced protein 93 (E93) is a determinant that promotes adult metamorphosis in both hemimetabolous and holometabolous insects. Krüppel-homolog 1 (Kr-h1), an early juvenile hormone (JH)-inducible gene, participates in the JH signaling pathway controlling insect metamorphosis. In the current study, an E93 cDNA (NlE93) and two Kr-h1 cDNA variants (NlKr-h1-a and NlKr-h1-b) were cloned from Nilaparvata lugens (Stål), one of the most destructive hemimetabolous insect pests on rice. Multiple sequence alignments showed that both NlE93 and NlKr-h1 shared high identity with their orthologs from other insects. The expression patterns revealed that decreasing NlKr-h1 mRNA level was correlated with increasing NlE93 mRNA level and vice versa. Moreover, RNAi assays showed that the knockdown of one of these two genes resulted in significantly upregulated expression of the other. Correspondingly, phenotypical observation of the RNAi insects revealed that depletion of NlE93 prevented nymph–adult transition (causing a supernumerary nymphal instar), while depletion of NlKr-h1 triggered precocious formation of incomplete adult features. The results suggest that Nlkr-h1 and NlE93 are mutual repressors, fitting into the MEKRE93 pathway. The balance between these two genes plays a critical role in determining the proper timing for activating metamorphosis of N. lugens during the nymphal stage.